The first reported case of possible Haemophilus influenzae type b vaccine failure from Kuwait and literature-review - Prashant Purohit; Ina'am Ahmad Al-Obaid; Nehad Gamal Al-Deen Omar (Elsevier, 2014)
Summary: A 17-month-old vaccinated Kuwaiti boy presented with meningitis. The Haemophilus influenzae type b (Hib) capsular antigen was detected in his blood, CSF and urine. The microorganism failed to grow in culture. This case represents the first report of possible Hib vaccine failure from Kuwait. This report examines the possible reasons for this failure by reviewing the literature and emphasizes the need to broaden the definition of vaccine failure with the aim of optimizing the timing of the vaccine booster dose for prematurely born children and establishing continuous surveillance for Hib vaccine failure. Keywords: Haemophilus influenzae type b vaccine failure, Haemophilus influenzae type b meningitis